Pedagogical Competences of Arabic Language Teachers at Madrasah Tsanawiyah in Pangkalpinang (Implementation and Obstacles) - Ela Isnani Munawwaroh; Niswatush Sholihah; Andi Kholilullah; Fouad Larhzizer (Mantiqu Tayr: Journal of Arabic Language, 2024)
During observations at Madrasah Tsanawiyah (MTs) in Pangkalpinang, We found that there were still many students who had poor Arabic language skills. It makes us interested to know the pedagogical competence of the teacher at the school and also the obstacles he encountered in optimizing the application of the pedagogic competence he possesses because there are some studies that say that the pedagogy of teachers influences the learning outcome, motivation, and interest in learning Arabic students. This research aims to find out how the teacher's pedagogical competence is implemented in the following learning process with the obstacles encountered by the teacher in implementing such pedagogic competence. This research used a qualitative approach with descriptive methods. For data collection, the methods of interviews, documents and observations were used. For data analysis, the techniques invented by Miles and Huberman consist of the process of data reduction, presentation of data, and drawing conclusions. The results of research showed that teachers at Madrasah Tsanawiyah (MTs) in Pangkalpinang already have good pedagogical competence. However, in optimizing the application of their pedagogical competences, teachers face various barriers from both students, schools, environments, and learning time. This research provides information to future researchers. We hope that there will be further research into solutions that can be offered to overcome barriers to learning Arabic that come from students, schools, environments and the learning time provided.